2016
DOI: 10.1007/s00266-016-0624-y
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Outcomes and Complications of Primary Fingertip Reconstruction Using Reverse-Flow Homodigital Island Flaps

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 43 publications
2
17
0
1
Order By: Relevance
“…The mean flap area was 294.4 mm 2 , similar to the studies found in the literature ( Table 3 ). 3 , 13 , 14 , 15 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean flap area was 294.4 mm 2 , similar to the studies found in the literature ( Table 3 ). 3 , 13 , 14 , 15 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Most patients maintained the range of motion (98.9%). Regmi et al 17 performed a systematic review and found an mean range of motion of 63° only of the distal interphalangeal joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis, done by Regmi et al .,[ 3 ] that included 8 studies and 230 fingertip injuries flap survival rate was 98% (including partial survival). In our study, all our flaps survived [ Figure 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are reliable and provide coverage with glabrous skin, which is a better match than dorsal skin. 5 The donor site is more concealed with better cosmesis, and the extensor tendon is not tethered.…”
Section: Sirmentioning
confidence: 99%